The study of degradation and mechanical properties of poly(lactic) acid (PLA) based 3D printed filament - Zainuddin, Muhammad Zulhilmi; Abu Bakar, Ahmad Adnan; Norjeli, Muhammad Faishal; Abdullah, Shahino Mah; Baharuddin, Ahmad Syukran; Alauddin, Muhammad Syafiq; Mohd Noor, Ikhwan Syafiq; Tamchek, Nizam; Alahmadi, Ahmed; Alforidi, Ahmad F; Mohd Ghazali, Mohd Ifwat (Institute of Physics, 2024)
Additive manufacturing, commonly known as 3D printing technology, has become one of the mainstream processes in the manufacturing industry due to its advantages over conventional manufacturing, which have piqued the public’s interest. This study aims to focus on the influence of thermal conditions on crystallization towards mechanical properties of 3D printed poly(lactic) acid (PLA) degradation samples with 100% infill. As for the degradation profile, the highest weight loss recorded by the samples was 0.7%, observed in samples buried in soil with an abiotic medium for one month. The exposure of degraded samples to high temperature during drying affected their crystallinity, resulting in significant changes in strains, particularly between week 1 and week 2, where strains dropped significantly from 7.33% to 4.28%, respectively. In conclusion, it has been demonstrated that degradation for PLA material still can occur in an abiotic medium, albeit at a slower rate compared to a biotic medium due to the presence of additional microorganisms and bacteria. Besides, the post-heat treatment process on PLA degradation samples affects their crystalline structure, resulting in significant changes in mechanical properties, particularly especially strains. Therefore, it can be concluded that different materials exhibit distinct mechanical properties.